Ответ:
or
Объяснение:
Составим уравнение:
Умножим на 3:
Умножим на: х*(х+4)
(3х-15)(х+4)=х(3х-24)+х(х+4)
3х²-3х-60=3х²-24х+х²+4х
-х²-3х+20х-60=0
х²-17х+60=0
По теореме Виета:
17=
60=
=12
=5
ТОГДА ДРОБЬ:
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение:
Составим уравнение:
Умножим на 3:
Умножим на: х*(х+4)
(3х-15)(х+4)=х(3х-24)+х(х+4)
3х²-3х-60=3х²-24х+х²+4х
-х²-3х+20х-60=0
х²-17х+60=0
По теореме Виета:
17=![x_{1}+ x_{2} x_{1}+ x_{2}](https://tex.z-dn.net/?f=x_%7B1%7D%2B%20x_%7B2%7D)
60=![x_{1} *x_{2} x_{1} *x_{2}](https://tex.z-dn.net/?f=x_%7B1%7D%20%2Ax_%7B2%7D)
ТОГДА ДРОБЬ: